Oral health and longitudinal changes in fasting glucose levels: A nationwide cohort study. - Tae-Jin Song (Public Library of Science (PLoS), 2021)
We investigated the association between oral hygiene indicators of periodontitis, tooth loss, and tooth brushing on the longitudinal fasting glucose level in non-diabetic subjects. Using a nationwide health screening database in Korea, we included non-diabetic individuals who received a health screening program with oral health check in 2009-2010. We constructed a linear mixed model for the longitudinal data of fasting glucose from the baseline to 2015. During the 4.84-year of median follow-up, 91,963 individuals (mean age 56.2 at baseline) underwent 392,780 health examinations with fasting glucose level (mmol/L). The presence of periodontitis was 39.3%. In the multivariate linear mixed analysis, periodontitis was related with increased fasting glucose levels (β = 0.0084, standard error = 0.0035, p = 0.018). Similarly, tooth loss was associated with increased level of fasting glucose (β = 0.0246, standard error = 0.0038, p < 0.001). Compared with tooth brushing ≤2 times/day, tooth brushing ≥3 times/day was associated with decreased fasting glucose levels (β = -0.0207, standard error = 0.0033, p < 0.001). Our data showed that periodontitis and tooth loss were associated with increased fasting glucose levels in non-diabetic individuals. The study findings imply that frequent tooth brushing may reduce fasting glucose levels. Further research is needed to determine the effect of periodontal intervention on glycemic control.